A risk management framework for cloud migration decision support - Shareeful Islam; Stefan Fenz; Edgar Weippl; Haralambos Mouratidis (Journal of Risk and Financial Management, 2017)
Managing risks is of paramount importance for enabling a widespread adoption of cloud computing. Users need to understand the risks associated with the process of migrating applications and data, so that appropriate mechanisms can be taken into consideration. However, risk management in cloud computing differs from risk management in a traditional computing environment due to the unique characteristics of the cloud and the users' dependency on the cloud service provider for risk control. This paper presents a risk management framework to support users with cloud migration decisions. In particular, the framework enables users to identify risks, based on the relative importance of the migration goals and analyzed the risks with a semi-quantitative approach. This allows users to make accurate cloud migration decisions, based on specific migration scenarios. Our framework follows basic risk management principles and proposes a novel and structured process and a well-defined method for managing risks and making migration decisions. A practical migration use case about collaborative application such as e-mail and document migration is considered to demonstrate the applicability of our work. The results from the studied context show that risks in cloud computing mainly depend on the specific migration scenario and organization context. A cloud service provider is not alone responsible for mitigating all the risks; hence, depending on the type of risk, the cloud user is also responsible for risk mitigation.
Keywords: 650; risk management framework; risk assessment; cloud migration; security; analytic hierarchy process (AHP); business value